Hubungan Kadar Zinc dan Pola Asuh Ibu dengan Kejadian Stunting pada Anak Usia 2 – 5 Tahun di Kecamatan Panti Kabupaten Pasaman - Elsa Noftalina; Mayetti Mayetti; Afriwardi Afriwardi (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Stunting is a short body condition based on height according to age (TB / U) whose standard deviation is less than -2 and -3 from the z-score calculation of the WHO child growth standard table. Stunting is an irreversible growth disorder due to inadequate nutrition and recurring infections during the first 1000 days of life. Indicators of chronic malnutrition that occur in a long time so that stunting in children under five, especially at the age of 2-5 years stunting will be clearly visible and is one indicator of chronic nutritional status that can provide an overall picture of the disorder in the past. The causes of stunting are lack of nutrition, infectious diseases, poor parenting, poor environmental sanitation and low health services. Zinc deficiency can cause impaired growth and decreased immunity. One of the biomarkers used is the analysis of hair zinc levels because it can describe chronic zinc levels in the past so it is appropriate to measure zinc levels in the stunting condition which is a long-standing condition of malnutrition. The croos sectional research design was carried out in the Panti District of Pasaman Regency and the West Sumatra Regional Health Laboratory in June to July 2019. The study sample were mothers and children aged 2-5 years as many as 60 people divided into two groups which are stunting and normal children, taken by proportional stratified simple random sampling. Zinc levels were measured by atomic absorption spectrophotometry (AAS) while parenting used questionnaires. Statistical test using Mann Whitney test and Chi Square. The results showed the mean zinc levels in stunting children 154.70 (9-387) µg / g and zinc levels in normal children 241.00 (60-933) µg / g with p = 0.018. parental feeding (p = 0.009), hygiene parenting (p = 0.034). health care parenting (p = 0.017), psychosocial stimulation parenting care (0,000). The conclusion of this study is that there is a significant association between zinc levels and parenting with the incidence of stunting.